Robust GMPHD filter with adaptive target birth - Ma, L.; Wang, P.; Xue, K.; Kim, Du Yong (2014)
© 2014 IEEE. Recently, the Gaussian Mixture Probability Hypothesis Density (GMPHD) filter has been studied as a popular method for multi-target tracking in clutter background. As an extended version, robust GMPHD filter, also known as the ?-GMPHD filter, was subsequently proposed to handle unknown clutter rate. In this letter, we use a Partially Uniform Birth (PUB) model for target births and present the ?-PUB-GMPHD filter, which accommodates tracking scenarios where targets can appear anywhere in the surveillance region and clutter rate is unknown. However, analysis of the ?-PUB-GMPHD filter demonstrates that clutter cardinality is underestimated due to the presence of PUB model and the cardinality bias of clutter is susceptible to spontaneous target birth rate. Hence, we propose adaptive birth rate technique for the ?-PUB-GMPHD filter to initialize new tracks quickly and simultaneously avoid severe cardinality bias. Simulations are present to verify the ?-PUB-GMPHD filter with proposed adaptive birth rate technique.